Tonsillar Plasmacytoma: clues on magnetic resonance imaging - İrfan Çelebi; Gülpembe Bozkurt; Nedim Polat (BMC Medical Imaging, 2018)
Abstract Background Malignant plasma cell proliferation may present as a disseminated disease (multiple myeloma), a solitary plasmacytoma of bone, or an extramedullary plasmacytoma of soft tissue. The latter plasmacytomas represent approximately 3% of all plasma cell proliferations, and 80% develop in the head-and-neck region. The unexpected clinical presentation of such masses may be present. Case presentation Here, we report a rare case of primary tonsillar plasmacytoma in a 42-year-old female. The patient presented with asymmetric tonsillar hypertrophy that was resistant to antibiotherapy. Upon further workup, we found no evidence of multiple myeloma or light-chain disease. The patient underwent surgery and, at the last follow-up, exhibited no evidence of such disease. Conclusions In adults presenting with asymptomatic tonsillar enlargement, the possibility of submucosal masses should be considered, thus encouraging the radiologist to evaluate crypts within the palatine tonsil on a postcontrast MRI, besides enlargement and signal change.